Equine Influenza and Equine Herpesvirus Vaccination: Evaluation of Immune Response and Safety of Concurrent Administration of Equip® FT and Equip® EHV 1, 4. (9th September 2013) - Paillot, R.; Ons, E.; Besognet, B.; Slootmans, N.; Thomas, A.; Salt, J.
Abstract : Aims: The concurrent administration of EHV1, 4 and EIV vaccines is not currently recommended. This study aimed to evaluate safety and immunogenicity of concurrent administration of Equip® FT and Equip® EHV1, 4 (treatment group T04) as compared with vaccination with Equip® FT (treatment group T02) or Equip® EHV1, 4 (treatment group T03) alone. Methods: Each treatment group included 10 ponies vaccinated on study Days 0 and 42. Immune responses to vaccine antigens were measured on Day 56. Tetanus antibody titres were determined with the toxin binding inhibition test (ToBI). Immunity to equine influenza virus (EIV) induced by vaccination was measured by single radial haemolysis (SRH; antibody response) and IFN gamma assay (a marker of cell‐mediated immunity; CMI). Immune responses to Herpesvirus 1, 4 were measured by complement fixation (CF) and IFN gamma assay. Results: Concurrent administration of EIV and EHV1, 4 vaccines was well tolerated. Concurrent administration was proven to be efficacious against tetanus with similar serological immune response of treatment group T04 as compared with T02. Mean SRH results for ponies that received both vaccines were above 85 mm 2 for A/eq/Borlange/91 and A/eq/Kentucky/98 antigens, a threshold associated with clinical protection against closely related EIV strains. The highest levels of IFN gamma response were measured in group T02. Although concurrent vaccination seemed to have an effect on both equine herpesvirus (EHV) serology and EHV CMI, EHV results obtained during this study were not conclusive and may have been influenced by a natural EHV‐4 infection occurring prior to study start. Conclusion and practical relevance: Concurrent administration of Equip® FT and Equip® EHV1, 4 was well tolerated and induced mean serum antibody levels consistent with clinical protection for tetanus and EIV. However, it was not possible to gather relevant information about the EHV immune response under the conditions of this study. Ethical animal research: The study was conducted under the Animal Health Trust Home Office Project License and with approval of the Zaventem Ethics Review Assessment team (Zoetis).Sources of funding: The study was sponsored by Pfizer/Zoetis Animal Health.Competing interests: Equip® FT and Equip® EHV1, 4 are owned by Zoetis, who sponsored this study. Romain Paillot reports no conflict of interest. All other authors are employed by the study sponsor.